An Efficient Procedure for Synthesis of Oximes by Grinding - LI, JI-TAI; CHEN, YAN-XUE; LI, XIAO-LIANG; DENG, HAI-JIAN (Asian Journal of Chemistry, 2010)
Grinding is a convenient and easily controlled method for synthesis of organic compounds. Condensation of aldehydes with hydroxylamine hydrochlorides leading to oximes has been achieved with high yield by grinding. The advantage of the present method seems to be simple, efficient and environmental friendly.